Effect of Using Different Types of Polymer on Shear Strength of Simply Supported High Strength Reinforced Concrete Beams - Saman Mustafa Kamal1; Jalal Ahmed Saeed (Sulaimani Journal for Engineering Sciences, 2020)
This work is an attempt to study shear behavior of high strength reinforced concrete (modified with different types of polymer) beams. Fourteen simply supported reinforced concrete beams under central load in two groups are tested (with and without stirrups). All beams have the same cross section of (300x200) mm, length of 1200mm with the same reinforcement. The main variables were the compressive strength, shear reinforcement, types, and percentages of the added polymer to study the shear behavior of beams. It has been found that by adding different types of polymer (powder and liquid) up to 1%, causes a reduction in water to cement ratio (w/c) from 0.35 to 0.23. The powder polymer improves the compressive strength for 39%, increasing of the splitting tensile strength (fsp) was 40%, improving the flexural strength (fr) was 64%.Whereas, the range of growth by using liquid polymer in compressive strength was 16%, increasing of the splitting tensile strength (fsp) was 16%, improving of the flexural strength (fr) was 59%. From these results and based on statistical analysis, a mathematical model has been drawn for high strength concrete modified with different types of polymer.